New methodology for the synthesis of chiral, non-racemic a-tertiary amine centres: application to the synthesis of the marine alkaloid lepadiformine - Andrijevic, Ana (Department of Chemistry, 2017)
The development of new methodology for the synthesis of a chiral, non-racemic quaternary carbon bearing an α-nitrogen (an α-tertiary amine or ATA) continues to be an active area of modern research in current synthetic organic chemistry. As a privileged biological scaffold, ATAs are widespread amongst bioactive natural products, providing an inspiration in their complex architecture to synthetic chemists in drug discovery programmes. Three experimental endeavours comprise this project, which are presented as separate sections of Chapter 2. The first part focuses on new methodology for all-carbon quaternization based on an auxiliary-based diastereoselective alkylation of an auxiliary-malonate, in which an imidazolidinone auxiliary provided excellent facial selectivities in the alkylation in conjunction with KHMDS as the base. Five derivatives were generated in high yields (>85 %) and selectivities (dr >95:5). Extension of the methodology to generate ATAs using the auxiliary-malonate system forms the basis of the second section. This was achieved via a modified Curtius rearrangement protocol performed on quaternary carboxylic acids, in turn obtained from a chemoselective cleavage of a PMB ester malonate-auxiliary system. The ATA products were obtained in high yields and with retention of stereoselectivity, and following the non-destructive removal of the auxiliary by methanolysis, produced enantioenriched α,α-disubstituted alanine and phenylalanine methyl esters. Additional steps on other suitable derivatives furnished α-quaternary proline and lysine derivatives, all in high ees (96 – 98 %). The methodology offers a general approach to the production of enantioenriched ATAs, and in particular, access to both natural and unnatural α,α-disubstituted amino acids. Application to an attempted synthesis of lepadiformine is described in the final section, whereby the ATA of the alkaloid is constructed in an acyclic form employing the newly developed methodology. Reductive (non-destructive) removal of the auxiliary provided an amino alcohol derivative that was further elaborated via a sequence involving ring-closing metathesis, hydrogenation, hydroxyl group oxidation and Grignard addition to afford a functionalised A-ring of lepadiformine A, with key functionality in place for elaboration to the target. However, dehydration of the tertiary alcohol from the Grignard step, although successful in a related model study, led to problems, bringing the total synthesis endeavour to a close. In spite of this setback, the divergent nature of the approach allows for new designs in the synthetic plan, particularly regarding the order of which the functionalised A ring from this work is elaborated into the A/B/C target.